SURVEI ETNOFARMAKOGNOSI DAN PROFIL KIMIA DARI 33 TUMBUHAN OBAT DI PURWAKARTA, INDONESIA - Fikayuniar, Lia; Abriyani, Ermi; Yunita, Dewi (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Traditional medicine practices in Indonesia have long utilised medicinal plants as the main foundation for public health resilience. This research aims to document local knowledge of medicinal plant usage and analyse its chemical profile to strengthen the scientific validity of traditional utilisation by the Purwakarta community. The methods used include ethnopharmacognosy surveys through semi-structured interviews with snowball sampling technique, specimen collection and identification, phytochemical screening of six groups of bioactive compounds, and qualitative-quantitative data analysis (UV, FUV, RFC, FL). The results show that there are 33 species of medicinal plants used by the communities of Taringgul Tonggoh and Wanasari villages, with leaves being the most utilised part (91% of oral usage). The Zingiberaceae family dominates the utilisation, while flavonoids and tannins were detected in the highest amounts in the phytochemical screening, supporting empirical claims as antioxidants, anti-inflammatory, and antimicrobial agents. These findings demonstrate the consistency between traditional practices and pharmacological potential, while also filling the gap in ethnopharmacognosy documentation in Purwakarta. The implications of this study strengthen the scientific basis for integrating local knowledge into modern pharmacy and open up opportunities for the development of phytopharmaceuticals based on local biodiversity.